DEVELOPMENT OF THE ECONOMIC MECHANISM CORPORATE GOVERNANCE - KILICHEVA FARIDA BESHIMOVNA; NASIMOV BAXTIYOR VASIYEVICH (International Journal of Innovations in Engineering Research and Technology, 2021)
The article analyzes the developed methodological approach to increasing the cost enterprises, allowing to take into account the characteristics of the enterprise, the general economic situation, and theinterests of the user by changing and streamlining indicators in the cost model.